HUBUNGAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA - Brenda Sophia Panjaitan (Klabat Journal of Nursing, 2020)
Abstract Elderly is the last phase in life that will experience setbacks which result in muscles weakness, degenerative disease, anxiety and depression. Elderly need support from others. Support from family is an important element to motivate the elderly, increase self-confidence, and assist the elderly inn meeting their needs and dealing with their problems. High family support will improve the quality of life of the elderly. This study aims to determine the relationship between family and quality of life of the elderly. The research was conducted using descriptive analysis method. Research respondent totalled 32 elderly men and women who were 60 years old or more and able to communicate well and were able to fill out questionnaires independently. The measuring instruments used are the WHOQOL-BREF as a quality of life questionnaire and the FSS (Family Support Scale) questionnaire for elderly people to measure family support. Keyword : Family Support, Quality of Life, Elderly